(untitled) (Journal of Comparative & International Higher Education, 2023)
Under the impact of globalisation, the graduate labour market has gone through various changes, which have resulted in the under-employment of new graduates in many countries. Although the Vietnamese government has launched numerous initiatives to develop employability for students, half of Vietnamese university graduates are unable to find jobs in their area of specialization. In order to address this issue, the Vietnamese HE sector has introduced the international career-oriented programs (ICOPs) to raise the quality of graduates and ensure that it is on par with international standards. This research focuses on three ICOPs to explore the interaction between teacher agency and student agency in enhancing graduate employability. This research draws on Bourdieu’s concepts of field, capital and habitus to investigate how academics and students perceive and exercise their individual agency. The position theory is adopted to shed light on the ways academics and students either comply with or disrupt the traditional hierarchical positioning within education systems to practice their co-agency. The study employs a qualitative approach with a combination of various data collection methods, including document analysis, interviews and focus groups to explore the role of teacher agency, student agency and their co-agency in enhancing graduate employability in Vietnam.